Effect of Flexible 3D Multipoint Stretch Bending Dies on the Shape Accuracy and the Optimal Design - Xiangfeng Lin; Yi Li; Zhongyi Cai; Jicai Liang; Ce Liang; Kaifeng Yu; Xiaoming Li; Aicheng Wang; Yanfei Liao (Advances in Materials Science and Engineering)
Aiming at the flexible 3D stretch bending with multipoint dies for the aluminum profile, the numerical simulation analysis of the bending process was carried out by ABAQUS finite element software. In the multipoint stretch bending (MPSB) process, the influence of the number of die units on the springback for the complex section profile was studied. The shape error between the forming parts and the target parts was reduced through the method of die surface modification. The results showed that the springback of the aluminum profile could reach a minimum when the number of die units was 25 under the precondition of saving cost and ensuring the quality of forming parts. In the numerical simulation, the maximum shape error of the forming parts reduced from 18.824 mm to 2.456 mm; in the test, the maximum shape error reduced from 27.26 mm to 6.03 mm through the method of die surface modification.